PENERAPAN MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI PENYAJIAN DATA BERBANTUAN MEDIA PAPAN DIAGRAM DI KELAS V SD - Christia Desiana Sidauruk; Yantoro; Andi Gusmaulia Eka Putri (Jurnal Tunas Pendidikan, 2024)
This research aims to describe the implementation of the use of the problem based learning (PBL) model in data presentation material assisted by diagram board media in class V elementary school to improve student learning outcomes. This type of research is Classroom Action Research (PTK). Research instruments include documentation, observation sheets, tests and interviews. The research subjects were class V students at SDN 80/I Muara Bulian, totaling 19 students, 11 students and 8 female students. The results obtained include the pre-action stage, the average score obtained by students was 43.33, then in the post test carried out in cycle 1 there was an increase in the average score of students, namely 66.31, and in the post test carried out in cycle 2, there was another increase in the average score, namely 80. Based on the results of the research, it can be concluded that the application of the PBL model assisted by diagram board media in improving student learning outcomes in class V elementary school has gone well and has increased